Using 222Rn to identify and quantify groundwater inflows to the Mundo River (SE Spain) - Ortega Ormaechea, Lucia (2015)
Groundwater discharge to the Mundo River (SE, Spain) has been investigated from 2011 to 2013 by means of 222Rn activities in river water and groundwater. Starting nearby the river source, some 50km of river channel have been studied. The Mundo River is located in the water stressed region of the Segura River Basin. Identifying and quantifying groundwater discharge to rivers is essential for the Hydrological Plan of the Segura Basin Authority. Four main areas of groundwater discharge to the river have been identified by means of 222Rn. Moreover, groundwater fluxes have been quantified using radon activities and, when possible, have been validated with chloride mass balances. The uncertainty range (±2σ) of all water balances has also been assessed. Groundwater discharge (QGW) values estimated by radon mass balances (RMB) and chloride mass balances (CMB) were similar in the river tracts and/or dates in which surface inputs from tributaries were null or negligible. This adds confidence to the QGW values estimated by RMB in the reaches were CMB could not be performed due to the existence of ungauged surface inputs, as is the case of the upper basin of the Mundo River, as well as to the applicability of the method to similar situations. Quantification of groundwater discharge allowed identifying Ayna zone as the main gaining reach of the studied area, with up to 29,553±8667m3day-1 in year 2011. Overall, the total QGW estimated by means of RMB for the studied area was 8-16% of the total river flow. The results are coherent with the meteorological conditions of the study period (average rainfall around 450mm/y) and also with the undisturbed situation of the aquifers discharging to the Mundo River in the considered area.